Development of Interactive E-Modules Based-Kvisoft Flipbook Maker Pro in Direct Learning on Redox Reaction Materials - Nurul Aulia Rahman; Erwinda R. Koroy; Deasy Liestianti; Sudir Umar; Topan Setiawan (EduLine: Journal of Education and Learning Innovation, 2022)
This study aims to develop an Interactive E-Module Based on Kvisoft Flip Book Maker Pro, its implementation of the level of students' understanding of redox reaction material. The interactive e-module referred to in this case is an electronic module that can be viewed through mobile devices and computers offline. The population and samples in this study were all students of class X MAN 1 North Halmahera for the 2021/2022 academic year, which amounted to 44 people and were spread in 2 different classes. Sample selection using saturated sampling techniques. The method used in this research is research and development. The product to be developed is an interactive E-Module based on Kvisoft Flip Book Maker Pro, with other supporting learning tools in the form of a syllabus, learning implementation plan (RPP), and practicum guide. The development model used from Plom consists of 5 stages, namely: 1) preliminary investigation, (2) design, (3) realization / construction, (4) evalusai and revision, (5) implementation. Product effectiveness trials are limited trials in the form of experimental research using the Two-Group Pretest Posttest research design. Research instruments are in the form of E-module validation and practicality sheets, student response assessment questionnaires, and learning outcomes assessment instruments. Data analysis uses descriptive and inferential analysis, using SPSS applications.